Does aid help improve economic institutions ? - Coviello, Decio (Policy research working paper, 2006)
"Aid is expected to promote better living standards by raising investment and growth. But aid may also affect institutions directly. In theory, these effects may or may not work in the same direction as those on investment. The authors examine the effect of aid on economic institutions and find that aid has neither a positive nor a negative impact on existing measures of economic institutions. They find the results using pooled data for non-overlapping five-year periods, confirmed by pooled annual regressions for a large panel of countries and by pure cross-section regressions. The authors explicitly allow for time invariant effects that are country specific and find the results to be robust to model specifications, estimation methods, and different data sets. "--World Bank web site